Daily, Sabbath, and festival prayers in the Dead Sea scrolls - Falk, Daniel K. (Studies on the Texts of the Desert of Judah, 1998)
All the evidence for daily, sabbath, and festival prayers in the Qumran scrolls is analysed in detail, document by document. On the basis of formal features and social-liturgical setting, these prayers are compared with each other to uncover divergent prayer traditions. Comparative material beyond the scrolls is used to reassess their place in the development of Jewish prayer. Evidence for prayers of different origin found at Qumran is important for reconsidering the nature of the scrolls, the community(s) which used them, and the history of Jewish liturgy. For several texts significant new reconstructions are offered.